A Qualitative Examination of COVID-19's Impacts on Physical Activity and Perceptions of Remote Delivery Interventions. Issue 3 (March 2022) - Brannon, Grace Ellen; Mitchell, Sophia; Ray, Madison A.; Bhai, Salman; Beg, Muhammad Shaalan; Basen-Engquist, Karen M.; Liao, Yue
Purpose: The COVID-19 pandemic is correlated with decreased physical activity (PA). Transitioning to remote work may impact people's acceptability and preferences for remotely delivered behavioral interventions, including PA. The objective was to examine perceptions of COVID-19 impacts on PA engagement and motivation, and perspectives related to remotely delivered PA interventions. Design: Cross-sectional small-group interview. Setting: Harris County, Texas. Participants: Insufficiently active, overweight/obese adults (16 healthy adults [aged 25–52 years], and 7 cancer survivors [aged 50–74 years]). Method: Group discussion was guided by semi-structured questions. Audio-transcribed data (278 pages) was analyzed using Braun and Clarke's process centering identification, analysis, organization, description, and reports. Results: Overall, participants expressed a decreased level of PA due to the pandemic. Difficulties (e.g., care-taking activities, working from home, and safety concerns) negatively affected motivation. Participants indicated high acceptability of remotely delivered PA interventions, with advantages of virtual technology features (e.g., did not have to maintain a gym membership) and even accountability in maintaining a PA routine (e.g., using virtual groups to engage in community support). Conclusion: Participants described COVID-19 negatively affects access to PA opportunities yet also expressed willingness to engage in remotely delivered PA interventions instead of in-person programs because of their COVID-19 experiences. Remote interventions can greatly increase accessibility and offer opportunities to provide personalized motivation and accountability that people need to be more physically active.